2016
DOI: 10.1080/00140139.2016.1175671
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of upper limb during the use of touch screen: motion strategies identification

Abstract: Nowadays touch technology is growing and developers try to make it ever more intuitive and easier to use. This present work focused on the upper limb joint coordination during the achievement of puzzles on touch screen. A 5-inch and 10-inch devices were used to perform 9 and 16 pieces puzzles dragged with digits. The conclusions showed an increase in joint solicitation with the number of piece and the touch screen size. Moreover, three interactions strategies proved to be an evidence: the 'wrist strategy' pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
0
15
0
4
Order By: Relevance
“…L'étude expérimentale s'appuie sur un essai contrôlé couplé à des actions sociales (histoire de vie, interactions sociales) en référence au tableau 1. Elle a été définie avec l'objectif de mise à l'épreuve des outils méthodologiques existants et de de Dupuy, Consel et Sauzéon [2016], eux-mêmes inspirés de la norme AttrakDiff [Lallemand et al, 2015], questionnaire sur le profil socioculturel, technologique et de santé, données issues des capteurs de mouvement [Jacquier-Bret et al, 2017], des mouvements oculaires [Caroux, Le Bigot et Vibert, 2011], des logs d'activités et des capteurs ambiants [Van den Bossche et al, 2016]). Ils permettent ainsi de répondre aux objectifs scientifiques des différents partenaires :…”
Section: Méthodologie D'évaluation Implémentéeunclassified
“…L'étude expérimentale s'appuie sur un essai contrôlé couplé à des actions sociales (histoire de vie, interactions sociales) en référence au tableau 1. Elle a été définie avec l'objectif de mise à l'épreuve des outils méthodologiques existants et de de Dupuy, Consel et Sauzéon [2016], eux-mêmes inspirés de la norme AttrakDiff [Lallemand et al, 2015], questionnaire sur le profil socioculturel, technologique et de santé, données issues des capteurs de mouvement [Jacquier-Bret et al, 2017], des mouvements oculaires [Caroux, Le Bigot et Vibert, 2011], des logs d'activités et des capteurs ambiants [Van den Bossche et al, 2016]). Ils permettent ainsi de répondre aux objectifs scientifiques des différents partenaires :…”
Section: Méthodologie D'évaluation Implémentéeunclassified
“…Jacquier-Bret et al observed users postures while carrying out their work on touch devices [15]. These researchers analysed which part of the body were used while executing common tasks and found that people's typical usage may increase the risk of developing musculoskeletal disorders.…”
Section: Studying Behaviormentioning
confidence: 99%
“…typing on a double-touchscreen laptop) or input factors (e.g. position of the screen, such as flat on the lap as identified by [15]).…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Various technologies can be used for tracking movements, such as optical motion-capture systems, large scale trackers, sensors embedded in mobile devices and touchscreens. In Human-Computer Interaction (HCI), the possibility of assessing the movements of users generated new perspectives for understanding and enhancing interaction [1,2], designing advanced interaction techniques [3,4] and manipulating objects in 3D virtual environments [5]. Human movement analysis is also at the heart of several disciplines impacting HCI such as biomechanics, physical medicine, gesture recognition, and signal processing.…”
Section: Introductionmentioning
confidence: 99%